Phenomenology of material:An engagement with graphite media through drawing as poietic revealing - Mohd Fuad Md Arif (2018)
The aim of this research is to phenomenologically engage with the graphite mediathrough drawing thus allowing the media to be disclosed in its poietic potentiality. The study alsoaims to interpret the media as a meaning-making entity. Methodologically, the two main aspects inthis research, The Drawing and The Writing, were combined through the phenomenology method ofepoch and reduction introduced by Max van Manen. As such drawing becomes a way for thegraphite media to be understood through the unfolding of drawing experience.Subsequently, reflection towards the artistic work and artworks through language becomes ameaning-making structure in expounding essential meanings. The results of this study haveunconcealed the media through four series of drawing bodies which are Matter at hand, 2015,Object-Tive TEXT, 2017, Reality hurts when you have nothing - Kuala Lumpur Biennale, 2017 andPhantoms, 2018. In conclusion, forms of abstract and ambiguous, paradoxical and equality,clear and unclear through lines that are erratic and grids, positive and negative have becomeessential marking in the open engagement of graphite media. As an implication, this studycan be used as a foundation to understand the position of artisticmaterials in artwork and meaning giving endeavor.